Should we be afraid of managed care? A theoretical assessment - Marcos Lisboa; Humberto Moreira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
Managed care capitation contracts provide monetary incentives for doctors to save medical costs while standard health insurance contracts do not. The paper proposes an alternative model for insurance markets which is used to analyze managed care contracts. In our model, households would like to buy insurance for the possible need of a service. The distinctive aspect of our model is that providers of service have privileged information on the most appropriate procedure to be followed. In the managed care application of the model, doctors are the providers of the service and through a diagnosis have better information of the patient's health condition. Equilibrium in our model is always constrained eÆcient. A partial capitation contract arises when both the cost and net benefits of treatment are high enough. We show that a capitation contract provides incentives for doctors: i) to care about the likelihood households will obtain the good state of nature (altruistic behavior); and ii) to save medical costs (managed care behavior). Doctors, in this case, choose less medically eÆcient treatments as they would choose under a standard health insurance contract. Besides this, household' welfare is increased in comparison to the standard contract. This increased welfare translates into a revealed preference for the capitation contract.
Keywords: 330